Jama’ah and collegial model in educational institutions: lessons and principles learned from Quran and Sunnah - Othman, Azam; Abu Bakar, Surayya; Faizuddin, Ahmad (IIUM Press, International Islamic University Malaysia, 2018)
Research on collegiality in the field of educational management and leadership has been conducted all over the world, but there were limited studies about collegiality from Islamic perspective. This article aims primarily to analyze the concept of collegiality from Islamic Perspective based on the Qur’anic and Sunnah principles and approaches, which may contribute to the awareness about its practice in educational institution. It also discusses a brief comparison between contemporary collegial models and Islamic perspective of collegiality. The result is expected to be a guideline for educational leaders to successfully apply the concept of collegiality in Islamic educational institutions. This paper argues that the concept of collegial model is related to the concept of “Jamaah”. Thus, it is vital for Muslims to highlight and advocate the Islamic principles of collegial model in the mainstream of intellectual discourse corpus. From the analysis of the relevant Qur’ānic verses and Hadiths, the research found that collegial model from Islamic perspective would enhance the collegiality culture in Muslim educational institutions. Muslim principals should pay attention to the goals of collegial model, organizational structures of collegial model, a